Assessment of Proximate and Sensory Properties of Potential Food Seasoning Made from Calabaza Squash (Cucurbita moschata) - Lorenz C. Gesta; Cleoh P. Quimson; Jahara F. Valledor; Angel Khryss C. Podadera; Carl Jarry O. Biol; Jade Stephanie B. Cerezo (Archives of Current Research International, 2025)
Aims: This study explores the potential of Calabaza Squash (Cucurbita moschata) seeds as a healthy and sustainable alternative to commercially available food seasonings, in response to increasing concerns over the health effects of excessive sodium, sugar, and unhealthy fats in conventional seasonings. Study Design: The researchers utilized a product developmental research design with a quantitative descriptive analysis method. This allowed for collecting and analyzing numerical data on the nutritional content and potential health benefits of Calabaza Squash (Cucurbita moschata) seeds as food seasoning. The participants were 21 professional chefs purposively selected from three restaurants in Surigao City. A two-part questionnaire, adopted and modified from Angeles et al. (2023), was used to gather demographic information and sensory evaluations (aroma, flavor, appearance, texture) using a 5-point Likert scale. Place and Duration of Study: This study was conducted from August 2023 to February 2024. The First Analytical Services and Technical Cooperative (F.A.S.T.) laboratory conducted nutritional content laboratory analysis. Methodology: Calabaza Squash seeds were cleaned, dried, roasted, and ground into a seasoning powder. The product was subjected to laboratory analysis to determine its proximate nutritional composition. Sensory evaluation was conducted by a panel of experienced chefs, assessing aroma, taste, texture, and appearance. Statistical analysis, including ANOVA, was applied to compare the sensory scores with those of a commercial seasoning. Results: The Calabaza Squash seed seasoning was found to contain carbohydrates (38.0%), proteins (21.6%), ash (16.0%), fat (18.4%), fiber (11.0%), and low moisture (5.96%), indicating good nutritional value and extended shelf life. However, sensory evaluation rated the seasoning as "Poor" in aroma, taste, texture, and appearance. Despite the low ratings, statistical analysis showed no significant difference (P > 0.05) between the Calabaza Squash seed seasoning and commercial seasonings in the evaluated sensory attributes. Conclusion: Calabaza Squash seeds demonstrate strong potential as a nutritious, plant-based seasoning alternative. While the nutritional profile is promising, improvements in flavor and texture are necessary to enhance consumer acceptability. The findings support the development of sustainable, health-oriented food innovations.